Effect of remifentanil on pre-osteoclast cell differentiation in vitro - Jeon, Hyun-Ook; Choi, In-Seok; Yoon, Ji-Young; Kim, Eun-Jung; Yoon, Ji-Uk; Cho, Ah-Reum; Kim, Hyung-Joon; Kim, Cheul-Hong (Journal of dental anesthesia and pain medicine: JDAPM, 2018)
The structure and function of bone tissue is maintained through a constant remodeling process, which is maintained by the balance between osteoblasts and osteoclasts. The failure of bone remodeling can lead to pathological conditions of bone structure and function. Remifentanil is currently used as a narcotic analgesic agent in general anesthesia and sedation. However, the effect of remifentanil on osteoclasts has not been studied. Therefore, we investigated the effect of remifentanil on pre-osteoclast (pre-OCs) differentiation and the mechanism of osteoclast differentiation in the absence of specific stimulus. Pre-OCs were obtained by culturing bone marrow-derived macrophages (BMMs) in osteoclastogenic medium for 2 days and then treated with various concentration of remifentanil. The mRNA expression of NFATc1 and c-fos was examined by using real-time PCR. We also examined the effect of remifentanil on the osteoclast-specific genes TRAP, cathepsin K, calcitonin receptor, and DC-STAMP. Finally, we examined the influence of remifentanil on the migration of pre-OCs by using the Boyden chamber assay. Remifentanil increased pre-OC differentiation and osteoclast size, but did not affect the mRNA expression of NFATc1 and c-fos or significantly affect the expression of TRAP, cathepsin K, calcitonin receptor, and DC-STAMP. However, remifentanil increased the migration of pre-OCs. This study suggested that remifentanil promotes the differentiation of pre-OCs and induces maturation, such as increasing osteoclast size. In addition, the increase in osteoclast size was mediated by the enhancement of pre-OC migration and cell fusion.